Meningkatkan Hasil Belajar Pendidikan Pancasila Menggunakan Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament bagi Siswa Kelas V SDN Bandar Lor 3 - Aziz, Alaik Zulfikar (Jurnal Simki Postgraduate, 2025)
This classroom action research was motivated by the inaccuracy of the model teacher in selecting the learning model, which resulted in boredom and lack of focus for students in following the learning process. This study aims to determine the "Effect of the Teams Games Tournaments (TGT) Cooperative Learning Model in Improving the Learning Outcomes of Fifth Grade Students in Pancasila Education Learning. The level of student focus in learning is still low, which results in low student learning outcomes, this is based on the results of observations that researchers have carried out. There are still many passive students. Therefore, researchers use the TGT type cooperative learning model to improve student learning outcomes. This study uses classroom action research. The subjects of this study were 20 fifth grade students of Bandar Lor 3 State Elementary School. As the object of research are observation, documentation, and test methods. In conducting data analysis, this study uses three components of activities, namely data reduction, data presentation and conclusion drawing. Based on the results of the study, there was an increase in student learning outcomes that can be seen from the achievement of test scores, namely: in Cycle II it has increased and it is said that the results of learning Pancasila education using the TGT cooperative learning model have been completed. This increase in student learning is increasingly visible in the test results in Cycle II, the remaining 4 students are below the incomplete score. Meanwhile, 16 completed the course, achieving a completion rate of 80%. This score exceeded the completion score by more than 70%. Therefore, during the final test of Cycle II, students achieved the minimum completion criteria (KKM) for the learning outcome test.